2005
DOI: 10.1088/0031-9155/50/14/008
|View full text |Cite
|
Sign up to set email alerts
|

Rigid-body transformation of list-mode projection data for respiratory motion correction in cardiac PET

Abstract: High-resolution cardiac PET imaging with emphasis on quantification would benefit from eliminating the problem of respiratory movement during data acquisition. Respiratory gating on the basis of list-mode data has been employed previously as one approach to reduce motion effects. However, it results in poor count statistics with degradation of image quality. This work reports on the implementation of a technique to correct for respiratory motion in the area of the heart at no extra cost for count statistics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 21 publications
0
69
0
Order By: Relevance
“…Reprinted from Rausch et al [181] with permission from Elsevier. [193], during PET-image reconstruction-motion compensation during image reconstruction (MCIR) [194], and after PETimage reconstruction [195]-Reconstruction Transform Average (RTA). Recent studies have been performed to evaluate the performance of these three methodologies [196,197].…”
Section: Motion Compensationmentioning
confidence: 99%
“…Reprinted from Rausch et al [181] with permission from Elsevier. [193], during PET-image reconstruction-motion compensation during image reconstruction (MCIR) [194], and after PETimage reconstruction [195]-Reconstruction Transform Average (RTA). Recent studies have been performed to evaluate the performance of these three methodologies [196,197].…”
Section: Motion Compensationmentioning
confidence: 99%
“…These last approaches are subject to noise amplification or computational issues. 8,19,20 In 2009, Werner et al 21 examined 18 patients with lung cancer and identified a significant decrease in tumour volume on images gated to respiratory movement compared with nongated images (244.5%, p 5 0.025). The gated tumour volume was not different compared with the volume obtained on the CT images.…”
Section: Introductionmentioning
confidence: 99%
“…In practical terms, the situation is further complicated because motion can be irregular [9,10] and non-periodic over the duration of a PET acquisition. Researchers have shown some success in estimating motion and correcting for it using PET data alone [11]; however, this can be limited for several reasons: (a) PET images acquired or gated over the short time frames necessary to capture motion are usually too noisy to employ non-rigid registrations [12]; (b) For tracers with rapid kinetics, the radioactivity varies significantly with time, depending on the physiological response of the patient to the tracer [13]; (c) For attenuation correction (AC) of PET images, AC factors need to be accurately registered with each PET position [14]; (d) PET has limited axial field of view (FoV) and cannot measure motion at the edges. A possible alternative approach that can be used to avoid these limitations is the use of a combined PET-MR scanner [15] capable of simultaneous PET and MR acquisition.…”
Section: Introductionmentioning
confidence: 99%